Corporate venture capital: common practices and different approaches cases research of Arezzo&Co’s ZZ Ventures and LVMH’s LVMH Luxury Ventures - Parnes, Paula (2022)
This paper aims to address common threads to creating a corporate venture capital and uses to exemplify two cases research: Arezzo&Co’s ZZ Ventures and LVMH’s LVMH Luxury Ventures. As such, the paper examines, first, how corporate venturing is a growing trend worldwide and uses qualitative and quantitative indicators to do so. Second, the study identifies what indicators are primordial in shaping a corporate venture unit within a company and does so by elaborating potential best practices to be used and considered when structuring said unit. Third, the paper then deep dives into two cases research, ZZ Ventures by Arezzo&Co and LVMH Luxury Ventures by LVMH, and details how said units came to be implemented. Comparative analysis of different CVCs were developed as to provoke the reader in understanding different manners of implementing such nucleus and imagine impacts each one might have within a specific corporation. After an in-depth analysis of the implementation process of a corporate venture capital nucleus, it can be said to be beneficial for the company, both in practical results as in the market’s opinion.